(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Enlightenment writer Abdulla Avloni to the development of the science of pedagogy made a significant contribution, is the most beautiful of the Uzbek people in his works reflected its traditions, important life issues related to education. It will be discussed about Abdulla Avloni’s meaningful life and his valuable works.